Altered states : globalization, sovereignty and governance - Smith, Gordon S. (Gordon Scott), 1941- (International Development Research Centre, 2000)
"In Altered States, Gordon Smith and Moises Naim explore the dynamics of globalization and discuss what makes today's globalization distinct. They test the prevailing wisdom about sovereignty and state capacity, and sort out the humbug. They consider whether sovereignty itself is an impediment or a requirement to security and prosperity. And, in three areas ripe for progress - preventing deadly conflict, providing opportunities for the young, and managing the many harms of climate change - they advance plans of action by which states, with others in the global community, can govern successfully in the future. Their message gives both hope and warning: globalization opens possibilities of prosperity, security, and human well-being, but only if new ways of governance are constructed."--Jacket.